URBAN FOREST STRUCTURE AND THERMAL COMFORT IN “OASIS CITIES” OF ARID ZONES. - Correa, Erica Norma (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2010)
Usually, cities settled in arid or semi-arid regions follow an urban development model based on compact morphologies as a bioclimatic strategy for the control of solar radiation. However, the reference case in this study, the city of Mendoza, Argentina, located also in a seismic and semiarid zone, has a different urban model. The city displays wide road channels and different tree species along the streets in opposition to the compact city model. In this scheme, the shadow is achieved through the urban forest structure. For these cities in dry-lands called "oasis cities" it is interesting to analyze in depth the effect of the different tree species and their green structures on the thermal balance of urban canyons. For this reason; this paper evaluates the thermal comfort conditions, in urban canyons of low building density forested with tree species of second magnitude, in summer. The results show that the observed thermal behavior and the thermal comfort conditions are clearly consistent with the characteristics of growth and development of forest configurations evaluated and its entailment with the climatic resources and morphology of the evaluated city.